Clinical hemodialysis experience with percutaneous arteriovenous fistulas created using the Ellipsys® vascular access system. Issue 2 (1st March 2019) - Hebibi, Hedia; Achiche, Jedjiga; Franco, Gilbert; Rottembourg, Jacques
Abstract: Introduction: The aim of this study is to report our clinical hemodialysis experience using a percutaneous arteriovenous fistula (pAVF) created with the Ellipsys® vascular access system. This pAVF device creates a permanent AVF anastomosis between the proximal radial artery (PRA) and the deep communicating vein (DCV) in the proximal forearm. Methods: The medical records of all patients with a pAVF were retrospectively reviewed. The clinical data analyzed included reliability of pAVF use, quality of dialysis, rate and success of puncture, and pAVF related complications, along with incidence of subsequent interventions. Findings: Between May 2017 and November 2018, 34 patients had a pAVF created with technical success in 33 patients (97%). Twenty‐eight out of 34 (82%) patients had successful two‐needle cannulation within 10 days to 6 weeks after pAVF creation. The mean Kt/v was 1.6 (1.2‐2) and the average recirculation was 10%. Fifteen patients (44%) needed no further access intervention. Twelve patients (35%) required an additional procedure to assist maturation of the pAVF in order to facilitate puncture. The average blood flow measured at the brachial artery, before the first cannulation, was 850 ml/min. From causes unrelated to the procedure, four patients died during the follow‐up study. Two patients required revision to a surgical AVF. None of the pAVFs developed aneurysmal degeneration steal syndrome, or high access flow related issues. Discussion: The Ellipsys® pAVF offers a safe and functional vascular access for hemodialysis. Advantages included prompt access maturation, avoidance of high flow AVFs, and a simple nonsurgical procedure with high patient satisfaction. Functional outcomes are equivalent and likely better than surgical fistulas. There appears to be less aneurysmal degeneration and need for future re‐intervention. Objective dialysis parameters indicate excellent quality of hemodialysis for the patient.